Comparison of 3‐year clinical outcomes between classic crush and modified mini‐crush technique in coronary bifurcation lesions. Issue 3 (3rd December 2012) - Yang, Hyoung‐Mo; Tahk, Seung‐Jea; Choi, So‐Yeon; Yoon, Myeong‐Ho; Lim, Hong‐Seok; Choi, Byoung‐Joo; Woo, Seong‐Ill; Joe, Dai‐Yeol; Seo, Kyoung‐Woo; Jin, Xiong Jie; Kim, Jin‐Woo; Hwang, Gyo‐Seung; et al.
<x xml:space="preserve">Abstract</x> Objectives We aimed to compare long‐term clinical outcomes between modified mini‐crush (modi‐MC) technique with classic crush (crush) technique for treatment of bifurcation lesions. Background The modi‐MC technique showed excellent procedural success and favorable 9‐month clinical outcomes. Methods From January 2005 to November 2009, we enrolled patients with de novo bifurcation lesions treated with modi‐MC (n = 112 lesions in 111 patients) and crush technique (n = 69 lesions in 67 patients). Primary endpoint was rate of major adverse cardiac events (MACE), a composite of all‐cause death, myocardial infarction (MI), and target lesion revascularization (TLR) at 3 years. Results There was no significant difference in baseline characteristics. The modi‐MC technique showed a significantly higher success rate of final kissing balloon inflation (84.1 vs. 98.2%, P = 0.001). After 3 years, MACE rate was significantly lower in the modi‐MC group (25.4 vs. 12.6%, P = 0.030). The incidence of all‐cause death was 7.5 vs. 2.7% (P = 0.087), MI was 4.5 vs. 1.8% (P = 0.290), TLR was 17.4 vs. 8.9% (P = 0.093) and stent thrombosis was 3.0 vs. 1.8% (P = 0.632) in the crush and modi‐MC groups, respectively. Conclusions The modified mini‐crush technique showed more favorable 3‐year clinical outcomes compared to the classic crush technique. © 2012 Wiley Periodicals, Inc.